Single cell analysis of human tissues and solid tumors with mass cytometry. Issue 1 (4th October 2016) - Leelatian, Nalin; Doxie, Deon B.; Greenplate, Allison R.; Mobley, Bret C.; Lehman, Jonathan M.; Sinnaeve, Justine; Kauffmann, Rondi M.; Werkhaven, Jay A.; Mistry, Akshitkumar M.; Weaver, Kyle D.; Thompson, Reid C.; Massion, Pierre P.; et al.
Abstract : Background: Mass cytometry measures 36 or more markers per cell and is an appealing platform for comprehensive phenotyping of cells in human tissue and tumor biopsies. While tissue disaggregation and fluorescence cytometry protocols were pioneered decades ago, it is not known whether established protocols will be effective for mass cytometry and maintain cancer and stromal cell diversity. Methods: Tissue preparation techniques were systematically compared for gliomas and melanomas, patient derived xenografts of small cell lung cancer, and tonsil tissue as a control. Enzymes assessed included DNase, HyQTase, TrypLE, collagenase (Col) II, Col IV, Col V, and Col XI. Fluorescence and mass cytometry were used to track cell subset abundance following different enzyme combinations and treatment times. Results: Mechanical disaggregation paired with enzymatic dissociation by Col II, Col IV, Col V, or Col XI plus DNase for 1 h produced the highest yield of viable cells per gram of tissue. Longer dissociation times led to increasing cell death and disproportionate loss of cell subsets. Key markers for establishing cell identity included CD45, CD3, CD4, CD8, CD19, CD64, HLA‐DR, CD11c, CD56, CD44, GFAP, S100B, SOX2, nestin, vimentin, cytokeratin, and CD31. Mass and fluorescence cytometry identified comparable frequencies of cancer cell subsets, leukocytes, and endothelial cells in glioma ( R  = 0.97), and tonsil ( R  = 0.98). Conclusions: This investigation establishes standard procedures for preparing viable single cell suspensions that preserve the cellular diversity of human tissue microenvironments. © 2016 International Clinical Cytometry Society